EGFR as a biomarker of smoking status and survival in oropharyngeal squamous cell carcinoma - Shanmugappiriya Sivarajah; Morris Kostiuk; Cameron Lindsay; Lakshmi Puttagunta; Daniel A. O’Connell; Jeffrey Harris; Hadi Seikaly; Vincent L. Biron (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background This study aims to investigate EGFR as a prognostic biomarker in oropharyngeal squamous cell carcinoma (OPSCC). Methods OPSCC patients from retrospective (1998–2009) and prospective cohorts (2014–2017) were included. Retrospectively collected tumors were used to construct tissue microarrays (TMAs), which were stained with EGFR, p16, DAPI and Pan-cytokeratin, and digitally quantified. EGFR, CDKN2A and HPV E6/7 levels from prospectively collected OPSCC was measured by droplet digital PCR (ddPCR). Biomarkers were compared to patient covariates, factors and survival outcomes. Results A total of 249 patients were included retrospectively and 64 patients were enrolled prospectively. p16 status (p < 0.001), smoking above 10 pack years (p = 0.04), smoking above 20 pack years (p < 0.001), total EGFR tumor levels (p = 0.016), and high EGFR within high or low Ki67 tumor nuclear staining (p = 0.03) were found to be significant predictors of 5-year disease specific survival (DSS). A Cox proportional hazard model of DSS showed smoking status and eGFR expression to be dependent of each other on predicting 5-year DSS. ddPCR analysis showed a significant association between smoking status and EGFR levels. Conclusions Total EGFR tumor levels are predictive of 5-year DSS. EGFR levels correlate with. smoking and could be an objective marker for this disease etiology.